PTU-166 An audit of the prevalence of faecal incontinence in hospital patients. (22nd June 2015) - Gumber, A; Redman, M; Elsharif, M; Kaur, G
Abstract : Introduction: Faecal incontinence (FI) is a common and under-reported problem, with many patients too embarrassed to seek help. Optimal management relies on first identification of these patients and only then- a thorough diagnosis that identifies all contributory factors, and a systematic approach to treatment. Management options include drug therapy, topical applications, containment products, behavioural techniques and surgery. Many patients do not receive optimal care due to lack of identification. In-hospital identification when they are admitted for other reasons may be one method of improving the care of such patients. Method: We assessed the identification of continence problems in our hospital patients via a simple 'spot check' audit of the different wards; we used the case notes for checking the documentation by both nursing and medical staff. We looked at care plans, stool charts, follow up plans etc. Results: Overall, 163 patient case notes were examined. 90% had nursing documentation about faecal continence documented in comparison to 48% for medical documentation. Of the 147 patients where nursing documentation was found, 10.8% were found to have FI. Only 31% of these patients would have been identified by medical documentation. If only medical documentation had been used, this would have dropped to 6.5%. Most of the patients that were identified as having FI were, as expected, elderly and on the stroke unit (44%), general elderly medical wards (37.5%), orthopaedic (12.5%) and gastroenterology (6%) wards. All patients (100%) were then referred appropriately for further management. Conclusion: Faecal incontinence has considerable impact on patients' lifestyle and quality of life, and can cause profound distress. It is important to identify these patients with FI, establish the cause and initiate appropriate management, whilst maintaining their privacy and dignity. The impact of FI on the patient's quality of life needs to be assessed prior to planning management/specialist referral etc. Written documentation in the form of care plans, follow up arrangements, advice leaflets etc is vital to providing optimal care for our patients. We found that our nursing documentation was much better than the medical documentation which needs to be improved. Once identified, all our patients were managed appropriately. Disclosure of interest: None Declared. References: Thomas TM, Egan M, Walgrove A, Meade TW. The prevalence of faecal and double incontinence. J Public Health 1984;6(3):216-220 National audit of continence care (NACC) Pilot audit evaluation report. June 2012